Pengaruh Pembelajaran Pendidikan Agama Islam Terhadap Akhlak Siswa Di Sd Negeri 023 Kebun Nenas Jake Kec. Kuantan Tengah Kab. Kuantan Singingi Provinsi Riau - Siregar, Syerlina; K, Khairuddin (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
to have good attitudes, behavior and habits in line with the Shari'a, both in relation to God, fellow creatures and the surrounding environment. So, PAI learning is expected to be able to grow and build students' morals so that they become better, especially for elementary school age children, at this age the peak of developing students' personalities who are very sensitive to various things around them. The aim of this research is to find out how much influence PAI learning has on student morals at SD Negeri 023 Kebun Nenas Jake District. Central Kuantan District. Kuantan Singingi Riau Province. This research includes ex post facto research which uses a quantitative approach. The research location is at SD Negeri 023 Kebun Nenas Jake, Kec. Central Kuantan District. Kuantan Singingi Riau Province. The research subjects were 46 students in grades IV and V who were Muslim. This research was conducted in May 2024. The data collection technique was a closed questionnaire. Data analysis techniques are normality tests, linearity tests, hypothesis tests (simple linear regression tests) and determination tests. Based on research findings that: there is an influence of PAI learning on students' morals at SD Negeri 023 Kebun Nenas Jake, proven by the normality test which obtained a variable (X) sign value. 0.293 > 0.05 and the student moral variable (Y) has a sign value of 0.528 > 0.05. Test the linearity of the sign value. equal to 0.980 > 0.05. Hypothesis test (simple linear regression test) with Sign level. amounting to 0.000 < 0.05, and from the determination test the magnitude of the relationship (R) was obtained, namely 0.574. And obtained a coefficient of determination (R Square) of 0.330, which means that the influence of Islamic Religious Education learning on student morals is 33%.